EXAMINING JOB STRESS AMONG INDONESIAN GEN Z EMPLOYEES USING JD-R MODEL - Hamdali, Natalia Tamara; Liswandi, Liswandi (Universitas IPWIJA (Sekolah Tinggi Ilmu Ekonimi IPWI Jakarta), 2023)
Job stress is an issue for Indonesian Gen Z to thrive in the workplace. This study aimed to examine job stress using the JD-R model. Job insecurity, workload, and work environment were used as independent variables. The research was conducted using quantitative research. 207 responses from Indonesian Gen Z employees working in startup/digital companies in Jakarta was gathered using questionnaire and statistical analysis was performed using IBM SPSS 26. This research found that all variables have partial and simultaneous impact towards job stress. This seeks for companies to practice transparency and feedback with employees about the job future, workload, and work environment, as well as building a company culture that encourages employee growth.Â Keywords: gen Z, JD-R model, job insecurity, job stress, workload, work environment